Incorporation of Salivary Gland Ultrasonography Into the American College of Rheumatology/European League Against Rheumatism Criteria for Primary Sjögren's Syndrome. Issue 4 (27th March 2020) - van Nimwegen, Jolien F.; Mossel, Esther; Delli, Konstantina; van Ginkel, Martha S.; Stel, Alja J.; Kroese, Frans G. M.; Spijkervet, Fred K. L.; Vissink, Arjan; Arends, Suzanne; Bootsma, Hendrika
Abstract : Objective: To assess whether the addition of salivary gland ultrasonography (SGUS) or replacement of current criteria items by SGUS influences the performance of the American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) criteria for primary Sjögren's syndrome. Methods: Included were consecutive patients with complete data on all ACR/EULAR items (n = 243) who underwent SGUS in our primary Sjögren's syndrome expertise center. Clinical diagnosis by the treating physician was used as the gold standard. Separate analyses were performed for patients who underwent labial or parotid gland biopsies. The average score for hypoechogenic areas in 1 parotid and 1 submandibular gland was determined (range 0–3). Next, performance of the ACR/EULAR criteria was evaluated after addition of SGUS or replacement of current items by SGUS. Results: Receiver operating characteristic analysis showed an optimal cutoff value of ≥1.5 for SGUS. The optimal weight for SGUS positivity was 1. Cutoff for ACR/EULAR fulfilment remained ≥4. In patients who underwent a labial gland biopsy (n = 124), the original criteria showed an area under the curve (AUC) of 0.965, sensitivity of 95.9%, and specificity of 92.2%. After the addition of SGUS, the AUC was 0.966, with a sensitivity of 97.3% and specificity of 90.2%. In patients who underwent a parotid gland biopsy (n = 198), similar results were found. Sensitivity of the criteria decreased substantially when SGUS replaced salivary gland biopsy or anti‐SSA antibodies, while performance remained equal when SGUS replaced the ocular staining score, Schirmer's test, or unstimulated whole saliva flow. Conclusion: Validity of the ACR/EULAR criteria remains high after incorporation of SGUS. With SGUS, clinicians are offered a larger array of tests to evaluate fulfillment of the ACR/EULAR criteria.